Women and comedy : history, theory, practice - Dickinson, Peter, 1968-; Higgins, Anne, 1952-; St. Pierre, Paul Matthew; Solomon, Diana, 1970-; Zwagerman, Sean (Fairleigh Dickinson University Press ; Co-published with the Rowman & Littlefield Publishing Group, Inc., 2014)
Women and Comedy: History, Theory, Practice brings together leading researchers from Canada, the United States, and Europe in an interdisciplinary collection of essays to chart the future of critical inquiry in gender and comedy studies.